Hold the Phone! Cell Phone-Related Injuries in Children, Teens, and Young Adults Are On the Rise - Peter W Guyon MD; Jamie Corroon ND, MPH; Karen Ferran PhD; Kathryn Hollenbach PhD; Margaret Nguyen MD (SAGE Publishing, 2020)
We describe trends in cell phone-related injuries in patients 21 years of age and under presenting to United States Emergency Departments. We calculated age-adjusted rates of cell phone-related injury per 100 000 individuals using data from the National Electronic Injury Surveillance System (NEISS) database and United States Census Bureau. From 2002 to 2015, an estimated 38 063 patients 21 years old and younger sustained a cell phone-related injury. The overall rate of injuries for all ages increased from 17.1 injuries per 100 000 in 2002 to 138 injuries per 100 000 in 2015, an increase of over 700%. The incidence of cell phone-related injuries increased across all age groups, with children 2 years of age and under experiencing the highest single incidence rate of 159 injuries per 100 000 in 2014. These findings highlight an important and relatively under-reported pediatric safety issue. Anticipatory guidance and injury prevention plans should be updated accordingly.